Centromere Positioning and Dynamics in Living Arabidopsis Plants - Fang, Yuda (The American Society for Cell Biology, 2005)
The organization and dynamics of the genome have been shown to influence gene expression in many organisms. Data from mammalian tissue culture cells have provided conflicting conclusions with regard to the extent to which chromatin organization is inherited from mother to daughter nuclei. To gain insight into chromatin organization and dynamics, we developed transgenic Arabidopsis lines in which centromeres were tagged with a green fluorescent protein fusion of the centromere-specific histone H3. Using four-dimensional (4-D) live cell imaging, we show that Arabidopsis centromeres are constrained at the nuclear periphery during interphase and that the organization of endoreduplicated sister centromeres is cell type dependent with predominant clustering in root epidermal cells and dispersion in leaf epidermal cells. 4-D tracking of the entire set of centromeres through mitosis, in growing root meristematic cells, demonstrated that global centromere position is not precisely transmitted from the mother cell to daughter cells. These results provide important insight into our understanding of chromatin organization among different cells of a living organism.